Beyond Intended Use: Adaptive Material Strategy (AMS) in Contemporary Window Design (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Architectural design has traditionally classified finishing materials according to predefined functional categories. Window sills, wall finishes, countertops, flooring, and façade materials have historically been selected based on established construction practices rather than their actual technical characteristics. However, contemporary interior architecture increasingly challenges these conventional boundaries. Advances in material engineering have created opportunities to rethink how architectural elements are designed by focusing on performance rather than intended use.This paper introduces the concept of Adaptive Material Strategy (AMS), a design framework that proposes selecting finishing materials according to their physical, technical, and aesthetic properties instead of their conventional classification. Using window architecture as a primary example, the paper demonstrates how innovative material adaptation expands design possibilities while improving durability, maintenance, spatial perception, and architectural expression.he proposed framework argues that contemporary architects should evaluate materials through a multidisciplinary lens that integrates engineering performance, environmental conditions, construction technology, and visual composition. Adaptive Material Strategy represents a shift from product-oriented specification toward performance-oriented architectural thinking.